2000
DOI: 10.1038/sj.bjp.0703457
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SB‐271046: A potent, selective and orally active 5‐HT6 receptor antagonist

Abstract: 3 In functional studies on human 5-HT 6 receptors SB-271046 competitively antagonized 5-HTinduced stimulation of adenylyl cyclase activity with a pA 2 of 8.71. 4 SB-271046 produced an increase in seizure threshold over a wide-dose range in the rat maximal electroshock seizure threshold (MEST) test, with a minimum e ective dose of 40.1 mg kg 71 p.o. and maximum e ect at 4 h post-dose. The level of anticonvulsant activity achieved correlated well with the blood concentrations of SB-271046 (EC 50 of 0.16 mM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(62 citation statements)
references
References 22 publications
1
61
0
Order By: Relevance
“…Some studies indicated that 5-HT 6 R antisense oligonucleotides (Bourson et al, 1995;Sleight et al, 1996) or 5-HT 6 R antagonists (Unsworth and Molinoff, 1994;Sleight et al, 1998;Bentley et al, 1999;Routledge et al, 1999) produced yawning-stretching behaviors that could be blocked by the muscarinic cholinergic antagonist atropine or potentiated by the cholinesterase inhibitor physostigmine. Other studies have implicated Rs in the modulation of cognitive processes (Russell and Dias, 2002).…”
Section: -Ht 6 R-influenced Behaviorsmentioning
confidence: 99%
“…Some studies indicated that 5-HT 6 R antisense oligonucleotides (Bourson et al, 1995;Sleight et al, 1996) or 5-HT 6 R antagonists (Unsworth and Molinoff, 1994;Sleight et al, 1998;Bentley et al, 1999;Routledge et al, 1999) produced yawning-stretching behaviors that could be blocked by the muscarinic cholinergic antagonist atropine or potentiated by the cholinesterase inhibitor physostigmine. Other studies have implicated Rs in the modulation of cognitive processes (Russell and Dias, 2002).…”
Section: -Ht 6 R-influenced Behaviorsmentioning
confidence: 99%
“…As SB-271046 failed to modify the retrieval performance when administered prior to the retrieval session, such an effect is specific to acquisition and consolidation. On the basis of pharmacokinetic considerations (Routledge et al, 2000), we speculate that SB-271046 administered 60 min before the first trial (acquisition) should interfere to a lesser extent with the consolidation processes than when injected just after the first session, and should thus mainly affect the acquisition phase. This hypothesis seems to be supported by the fact that the beneficial effect of 5-HT6R blockade seems more robust on consolidation (Figure 2b) than on acquisition because this latter effect shows a tendency to decrease with time ( Figure 1b).…”
Section: -Ht6r Blockade Improves Memory V Da Silva Costa Et Almentioning
confidence: 99%
“…administration, the peak concentration of SB-271046 in the blood would be obtained for a much shorter time, and clearance of the antagonist would be more rapid, than after p.o. administration (peak value at 180 min; Routledge et al, 2000). Under this scenario, administration of SB-271046 60 min before the first trial (acquisition) should have a maximal effect on the acquisition process while preserving the consolidation phase.…”
Section: Experiments 1: Effects Of 5-ht6r Blockade On Spatial Recognitmentioning
confidence: 99%
See 1 more Smart Citation
“…During this decade or so, there was a plenty of chemistry developed around different nuclei including the indole-based ones or even much simpler biphenyl sulfones and sulfonamides [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]34 ( Figure 2). Suven has reported several series of 1-sulfonylindoles bearing the amino group at 3 or 4 or 5 position of the central core [31][32][33] .…”
Section: Introductionmentioning
confidence: 99%